Analisis Pemajakan Atas Revaluasi Aset Tetap Di Indonesia: Tinjauan Literatur - Nasikhudin (Jurnal Pajak dan Keuangan Negara (PKN), 2024)
This research aims to analyze the regulation of assets revaluation for tax purposes in Indonesia and provide other alternatives besides the imposition of final Income Tax (PPh). This research is motivated by the practice of revaluation of fixed assets in the business which is commonly carried out but is not accompanied by high tax revenues from Final Income Tax payments on the revaluation of these assets. This means that taxpayers prefer to revaluate fixed assets for commercial purposes and not for tax/fiscal purposes. The law gives the Minister of Finance the authority to regulate taxation on the revaluation of fixed assets and it is known that apart from the imposition of Final Income Tax, the Minister of Finance can choose another alternative that has been regulated by the Income Tax Law, namely by indexing depreciation costs as has been done in setting the debt to equity ratio (DER). Penelitian ini bermaksud menganalisis pengaturan revaluasi tetap untuk tujuan perpajakan di Indonesia serta memberikan alternatif lain selain pengenaan Pajak Penghasilan (PPh) final sebagaimana diatur dalam aturan terkininya. Penelitian ini dilatarbelakangi oleh praktik revaluasi aktiva tetap di dalam dunia bisnis yang sudah biasa dilakukan, namun tidak dibarengi dengan tingginya penerimaan pajak dari pembayaran PPh Final atas revaluasi aset tersebut. Hal ini berarti wajib pajak lebih memilih merevaluasi aset untuk tujuan komersial namun tidak dilakukan untuk tujuan perpajakan/fiskal. Undang-undang melimpahkan kewenangan kepada Menteri Keuangan untuk mengatur pemajakan atas revaluasi aset tetap tersebut dan diketahui selain pengenaan PPh Final, Menteri Keuangan dapat memilih alternatif lain yang sudah diatur UU PPh yaitu dengan melakukan indeksasi biaya penyusutan seperti yang telah dilakukan pada pengaturan debt to equity ratio (DER).